Silencing of specificity protein 1 protects H9c2 cells against lipopolysaccharide-induced injury via binding to the promoter of chemokine CXC receptor 4 and suppressing NF-κB signaling. Issue 2 (1st February 2022) - Zhu, Zhao; Zhang, Guoxiu; Li, Dahuan; Yin, Xiaojun; Wang, Tianzhong
ABSTRACT: G protein-coupled protein receptor CXC chemokine receptor 4 (CXCR4) has been shown to be involved in the development of sepsis; however, it remains unclear whether CXCR4 participates in the septic myocardial injury. In our study, treatment with lipopolysaccharide (LPS) increased the expression of specificity protein 1 (SP1) and CXCR4 in H9c2 cells. Notably, a positive association between SP1 and CXCR4 expression was observed in LPS-treated H9c2 cells, and SP1 positively regulated CXCR4 expression in H9c2 cells. Moreover, silencing of SP1 or CXCR4 suppressed LPS-induced inflammation and cell apoptosis in H9c2 cells, as evidenced by the increase in cell viability and decrease in lactate dehydrogenase release, interleukin (IL)-6, IL-8, and tumor necrosis factor (TNF)-α levels, and caspase-3 activity. Additionally, overexpression of CXCR4 abolished the protective effects of SP1 silencing on LPS-induced injury in H9c2 cells. SP1 was also shown to enhance the promoter activity of CXCR4 by directly binding with the binding motif site – 109/–100 in CXCR4 promoter. Besides, downregulation of SP1 or CXCR4 blocked LPS-induced activation of the NF-кB signaling in H9c2 cells. Furthermore, inhibition of NF-кB signaling by DHMEQ abolished LPS-induced myocardial inflammation and apoptosis. In conclusion, silencing of SP1 protected H9c2 cells against LPS-induced injury by binding to the promoter of CXCR4 and suppressing the NF-κB signaling pathway. Hence, our findings provide evidence that manipulation of SP1 or CXCR4 may be an effective approach to promote prevention or recovery of septic myocardial injury, and thereby, may serve as a potential therapeutic strategy for sepsis.